PARTISIPASI KELUARGA DALAM MENJAGA KEBERSIHAN DRAINASE DI AIR CAMAR KELURAHAN PARAK GADANG TIMUR KECAMATAN PADANG TIMUR - Endjelina, Sindy Putri; Erita, Yeni; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information, analyze and discuss data on Family Participation In Maintaining Cleanliness Air Camar Village Water Drainage in East Parak Gadang Eastern District of Padang.Â This type of research was descriptive correlation. The study population was a whole family living in the study area based on data and reports from the village numbered Parak East Tower (1985) KK. Samples were taken in 2 ways, samples taken 3 areas sampled area, the reason for the 3 areas of research have considerable number of households and the state of drainage is also less well preserved, the sample of respondents drawn using random sampling with proportional system the proportion of 10% so that the sample was 105 KK.Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) There is a family caring relationships with family participation in maintaining the cleanliness of the water drainage Â Air Camar Parak Gadang East Village District East Padang accounted for 29.5% of the family participation in maintaining the cleanliness of water drainage Air Camar Parak Gadang East Village District East Padang, (2) There is a relationship with the family of environmental knowledge family participation in maintaining the cleanliness of the water drainage Air Camar Parak Gadang East Village District East Padang, with a large contribution of 7.8%, ( 3) There is a relationship between knowledge family leisure time with family participation in maintaining the cleanliness of the water drainage Air Camar Parak Gadang East Village District East Padang, with a large contribution of 39.8% and (4) There is a significant and positive relationship between knowledge, knowledge of family environment and time free together with the participation of the family in maintaining the cleanliness of water drainage Air Camar Parak Gadang East Village District East Padang, with a large contribution of 46.0%.